Higher Education in Madhya Pradesh : The Way Forward - World Bank (Washington, DC, 2014)
Madhya Pradesh is fast emerging as a repository of skilled human resource. Investment on building up of human capital is showing upward trend. The State Government has focused attention on improving the quality of higher education along with its expansion by promoting public-private partnership. Legislation for encouraging establishment of private universities is expressive of state's resolve to become a hub of higher education. The 11th five year plan has set its goals as 'expansion of enrolment in higher education with inclusiveness, quality and relevant education, with necessary academic reforms in the university and college system. The goal is to set India as a nation in which all those who aspire to good quality higher education can access it, irrespective of their paying capacity'. Expansion, inclusion and quality are thus the three cornerstones of our national goals in education. The Government has set a target of 21percent Gross Enrolment Ration (GER) by the end of the twelfth plan (2017) with an interim target of 15 percent by the end of the eleventh plan 2012. This seems a highly ambitious aim considering the present GER of 12.4 percent. The Government of Madhya Pradesh convened a conference 'Higher education in Madhya Pradesh the way forward' on 3rd of October 2011 in Bhopal, Madhya Pradesh. The conference brought together key policy makers, academic faculty and stakeholders in the field of education to discuss the needs of higher education in Madhya Pradesh, and options for improvement and expansion. The Government of Madhya Pradesh is considering a reform of their higher education system, focusing first on the governance and legislative framework. In Madhya Pradesh, there are currently 15 universities, of which 9 are public. Further, there are over 300 colleges, a few of which have been awarded autonomous status and centers of excellence by the University Grants Commission (UGC), and the remaining are affiliated colleges. Governance plays an important role in the performance of any organization involved in public service. In a federal country with a written Constitution governed by rule of law, every activity in the public sphere is to be organized according to the framework prescribed by the law and the Constitution. It is therefore important to appreciate the legal framework under which higher education is organized in India and to begin the reform proposals with the law on the subject.